2019
DOI: 10.22271/ortho.2019.v5.i3m.1620
|View full text |Cite
|
Sign up to set email alerts
|

Role of external fixator in surgical management of intra-articular distal radius fractures: Functional and radiological outcomes

Abstract: The main aim of this study is to evaluate functional and radiological outcomes after treatment of intra-articular distal radius fractures by close reduction external fixation. Materials and Methods: Twenty five patients of intra-articular fracture distal radius fulfilling the inclusion criteria were treated between Jan. 2016 to Nov. 2017 with close reduction external fixation using principle of ligamentotaxis. The fixator was removed after 6-8 weeks and patients were followed up for 6 months postoperatively. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This was in disagreement with P. Kamra, et al, 2019 who found that the usual type of fracture in their study was AO type C1 (32%). (14)…”
Section: Discussionmentioning
confidence: 99%
“…This was in disagreement with P. Kamra, et al, 2019 who found that the usual type of fracture in their study was AO type C1 (32%). (14)…”
Section: Discussionmentioning
confidence: 99%